The Effect of Sugarcane Water Subtitution as a Candidate Substitute for Fructose in CEP Diluent on Spermatozoa Quality of Friesian Holstein Bull during Frozen Storage - Johana Dian Rahayu; Nur Ducha (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2022)
Sugarcane water contains sucrose which function as an energy source to increase ATP and motility of sprematozoa. The purpose of this study was to determine the effect of sugarcane water substitution as a candidate for fructose substitute in CEP diluent on the sperm quality of Friesian Holstein (FH) bull in frozen storage. The type of research used was experimental research with Completely Randomized Design (CRD) with 5 treatments and 4 repetitions, namely A (CEP); B (CEP without fructose + 15% sugarcane water); C (CEP without fructose + 20% sugarcane water); D (CEP without fructose + 25% sugarcane water); E (CEP without fructose + 30% sugarcane water). Parameters used were motility, viability, and membrane integrity of FH bull spermatozoa. The motility test was observed with a 400x magnification microscope. The viability test was carried out with eosin-negrosin dye and observed with a 400x magnification microscope. The membrane integrity test was carried out with HOST fluid and observed with a 400x magnification microscope. Data analysis used the Kolmogorov-Smirnov test, then the One-Way ANOVA test and Duncan’s test. The result showed that the treatment with CEP diluent had the best results in maintaining the quality of spermatozoa during frozen storage with an average motility, viability and membrane integrity of 40,11±0,41%; 46,71±0,15% and 45,88±0,77% respectively.